2022
DOI: 10.1038/s41598-022-20075-0
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 sensitizes the anti-cancer effects of sunitinib by inducing cell cycle arrest in renal cell carcinoma

Abstract: Sunitinib, a VEGF blockade, is used to treat clear cell renal cell carcinoma (ccRCC). However, the anti-cancer treatment effects of sunitinib do not last long in ccRCC patients. Ginsenoside, a natural medicine extracted from ginseng, has been studied in cancer treatment and shown to have anti-tumor effects and low toxicity. We assessed cell viability and cell cycle analysis in ccRCC cell lines after treatment with ginsenoside and sunitinib. DNA damage was evaluated by measuring 8-OHdG levels and comet assay. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Hwang et al revealed that Sunitinib has an antitumor effect. The cell cycle of renal cancer is blocked by Ginsenoside Rh2, which sensitizes the effect of Sunitinib and slows down the tumor progression (26). In the cell cycle, the mitotic G1 phase and G1/S transition checkpoint are important steps.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al revealed that Sunitinib has an antitumor effect. The cell cycle of renal cancer is blocked by Ginsenoside Rh2, which sensitizes the effect of Sunitinib and slows down the tumor progression (26). In the cell cycle, the mitotic G1 phase and G1/S transition checkpoint are important steps.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which GRh2 synergizes with sunitinib to cure ccRCC was investigated by Hwang et al The results showed that combined treatment with GRh2 and sunitinib enhanced G2/M blockade and DNA damage enhancement (upregulation of 8-OHdG expression), demonstrated inhibitory effects on ccRCC cell viability, and was validated in vivo. In combination with sunitinib, GRh2 provides a new therapeutic option for patients with ccRCC (19).…”
Section: Chinese Herb Monomer 21 Ginsenosidesmentioning
confidence: 99%
“…Many studies show that ginsenosides, especially triterpene saponins, are the main active ingredients in ginseng, which are composed of ginsengenin and sugar through an ether bond . Among them, ginsenoside Rh 2 (Rh 2 ) (Figure ) has been adequately investigated and exhibits remarkable functions including antitumor, anti-inflammatory, and antiallergic effects and enhancement of immune activity. It is widely used to resist liver cancer, leukemia, cervical cancer, prostate cancer, colon cancer, breast cancer, etc. Several recognized anticancer mechanisms of Rh 2 include (1) inducing apoptosis and autophagy of cancer cells; (2) triggering cycle arrest of cancer cells; (3) inhibiting invasion, migration, and metastasis of cancer cells; , and (4) suppressing angiogenesis and epithelial–mesenchymal transition (EMT). , …”
Section: Introductionmentioning
confidence: 99%
“… 3 6 It is widely used to resist liver cancer, leukemia, cervical cancer, prostate cancer, colon cancer, breast cancer, etc. 7 12 Several recognized anticancer mechanisms of Rh 2 include (1) inducing apoptosis and autophagy of cancer cells; 13 (2) triggering cycle arrest of cancer cells; 14 (3) inhibiting invasion, migration, and metastasis of cancer cells; 15 , 16 and (4) suppressing angiogenesis and epithelial–mesenchymal transition (EMT). 17 , 18 …”
Section: Introductionmentioning
confidence: 99%